PENERAPAN ARSITEKTUR METAFORA PADA MUSEUM GALUNG LOMBOK DI KABUPATEN POLEWALI MANDAR - Azis, Baso Muhammad Mudzar; Alfiah, Alfiah; Musdar, Muhammad Ajwad (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Polewali Mandar Regency has strong historical and cultural values, one of which is reflected in the Galung Lombok tragedy as an important part of the collective memory of the Mandar community. However, these historical values have not yet been fully incorporated into an educational facility that can visually and emotionally convey the meanings of struggle, loss, and resilience. This study aims to design the Galung Lombok Museum in Polewali Mandar Regency using a metaphorical architectural approach as a medium for historical preservation and the strengthening of local cultural identity. The method used is a descriptive qualitative method, with data collected through literature reviews, field surveys, interviews, and previous studies. The data were analyzed to formulate a design concept that aligns with the historical values of the Galung Lombok and Mandar cultures. The design results show that the metaphorical architectural approach is applied through building form, façade design, spatial layout, and supporting elements. The building form represents the journey of history, the crack symbolizes collective wounds, and the tip of the Sandeq boat inspires the Lamba’na façade as a symbol of maritime identity and struggle. In contrast, the Uai façade symbolizes the flow of a river, representing time continuity, life, and healing. Thus, the Galung Lombok Museum is expected to become a space for education and reflection, as well as a cultural icon that preserves the historical memory of the Mandar community.